MIDWIFE CARE IN NY. W 29 YEARS OLD WITH RETENTION OF PLACENTA IN THE MIDWIFE CLINIC L. PANGARIBUAN VILLAGE SIMANTIN PANE DAME OF THE YEAR 2020 - Sihombingr, Chintani; Cui, Zhenyu; Aulia Nanda, Ficha; Jusnita Samosir, Herna; Mazdalifah, Nur (International Conference on Health Science, Green Economics, Educational Review and Technology, 2021)
This study aims to determine the midwifery care in NY. W 29 years old with retained placenta at the L.pangaribuan midwife clinic in Simantin Pane Dame village in 2020. The results of the study show thatIn the study of the case of the mother in the third stage of labor in Mrs. W aged 29 years with retained placenta, subjective data was obtained with the main complaint, namely the mother felt worried because the placenta had not yet been born, the mother felt tired and weak and the mother said that in the first delivery she had done manual placenta. While objective data obtained general state data is weak,composmental Consciousness, TTV : BP : 110/70 mmHg,Q:78x/i, T : 36 0C,RR : 24x/i,umbilical cord does not extend at the vulva,bleeding ± 150 cc,placenta not delivered after 30 min, weak contractions,TFU : as high as the center. Based on this, there is no gap between theory and practice.Anticipating potential problems made to Mrs. W 29 years old with retained placenta is to put infusion + oxytocin 20 units in 500 cc RL, give metergin 10 units/IM and antibioticsCeftriaxone 3cc and the placenta was done manually, but in anticipating the problem of infection was still high because long gloves were not provided in the manual procedure of the placenta. Based on this found a gap between theory and practice.